A new species of Cricosaurus (Thalattosuchia: Crocodylomorpha) from southern Germany: the first three-dimensionally preserved Cricosaurus skull from the Solnhofen Archipelago. (5th February 2021) - Herrera, Yanina; Aiglstorfer, Manuela; Bronzati, Mario
Abstract : Cricosaurus represents one of the most important radiations within Metriorhynchidae, a specialized marine clade of Crocodylomorpha that flourished in marine environments from the Middle Jurassic until the Early Cretaceous. Here, we describe a new species of Cricosaurus, Cricosaurus rauhuti sp. nov., from the Mörnsheim Formation (lower Tithonian) of southern Germany. The specimen is the first three-dimensionally preserved Cricosaurus from this realm, and it is represented by a partially preserved cranium and lower jaw that has autapomorphic characters that distinguish it from any other species of Cricosaurus . The phylogenetic analysis shows that the new species is more closely related to some non-European forms from the Late Jurassic and one taxon from the Valanginian of Germany (all 3D-preserved) than to other Late Jurassic Cricosaurus from southern Germany (all 2D-preserved). Our exploratory analyses confirm that this is not a preservation bias. For the first time, this shows that there are two clades of Cricosaurus present during the Late Jurassic in Germany. Furthermore, it provides additional evidence of a close faunal relationship between Europe and South America in the Late Jurassic, as also evidenced by the fossil record of other marine reptiles. Finally, the distribution of metriorhynchids in localities of the Solnhofen Archipelago suggests a change in the taxic diversity of the region during the early Tithonian, which might be the result of environmental changes in the Solnhofen Archipelago. http://zoobank.org/urn:lsid:zoobank.org:pub:488705BF-AEAD-4F02-BB4E-429E3117BCD1